2023
DOI: 10.1093/clinchem/hvad169
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment of SARS-CoV-2 Antibodies in Oral Fluids Following Infection and Vaccination

Christopher D Heaney,
Heidi Hempel,
Kate L DeRosa
et al.

Abstract: Background SARS-CoV-2 variants continue to circulate globally, even within highly vaccinated populations. The first-generation SARS-CoV-2 vaccines elicit neutralizing immunoglobin G (IgG) antibodies that prevent severe COVID-19 but induce only weak antibody responses in mucosal tissues. There is increasing recognition that secretory immunoglobin A (SIgA) antibodies in the upper respiratory tract and oral cavity are critical in interrupting virus shedding, transmission, and progression of dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Another consideration is that for SARS-CoV-2 at least there is a strong congruence between oral fluids and DBS (K. DeRosa, N. Pisanic, K. Kruczynski, L. Styer, M. Parker, C. Heaney, and N. Mantis, manuscript in preparation). Thus, DBS and oral fluids might potentially be used interchangeably as means to survey large cohorts for immunity and vaccine responsiveness (32). A.…”
Section: Discussionmentioning
confidence: 99%
“…Another consideration is that for SARS-CoV-2 at least there is a strong congruence between oral fluids and DBS (K. DeRosa, N. Pisanic, K. Kruczynski, L. Styer, M. Parker, C. Heaney, and N. Mantis, manuscript in preparation). Thus, DBS and oral fluids might potentially be used interchangeably as means to survey large cohorts for immunity and vaccine responsiveness (32). A.…”
Section: Discussionmentioning
confidence: 99%
“…The latest report from 2023 announced 183 vaccines in the clinical phase and 199 in the preclinical phase [4]. Vaccines have shown that they are capable of inducing the formation of antibodies against SARS-CoV-2 [5][6][7], which makes them a good strategy for the prevention of new infections. However, other short-term strategies are needed to treat patients with severe conditions [8,9].…”
Section: Introductionmentioning
confidence: 99%